Littlewood-Paley Operators on Morrey Spaces with Variable Exponent - Shuangping Tao; Lijuan Wang (The Scientific World Journal)
By applying the vector-valued inequalities for the Littlewood-Paley operators and their commutators on Lebesgue spaces with variable exponent, the boundedness of the Littlewood-Paley operators, including the Lusin area integrals, the Littlewood-Paley g-functions and gμ*-functions, and their commutators generated by BMO functions, is obtained on the Morrey spaces with variable exponent.